Grain mineral composition of Argentinean-adapted wheat cultivars: a case study - D'amico, Iván Franco; Silva, Mauro; Moriconi, Jorge I.; Santa-María, Guillemo E.; Bainotti, Carlos Tomas; Tabbita, Facundo (CSIRO, 2021)
Abstract. Improvement of the nutritional quality of wheat (Triticum aestivum L.) has been quite challenging, due, in part, to the limited variation found in modern cultivars and the strong effect exerted by the environment, which hinder the selection process. The aim of this study was to characterise the mineral profile of grains of 35 Argentinean-adapted, mostly spring wheat cultivars in two successive years. Concentrations of most mineral nutrients in grains spanned approximately a two-fold range. Our study revealed a strong effect of the environment, but also that some key differences among genotypes are maintained over years. Correlation and principal component analyses showed the existence of a strong and stable association of variables determining the global elemental profile in grains of the wheat lines under analysis. In this regard, some cultivars displayed, over successive years, opposite global patterns of elemental composition, suggesting the existence of a genotype dependent ionome signature. Important negative correlations were found for the concentration of most, but not all, nutrients with yield, thus indicating a potential compromise among beneficial traits. The genotypic variation characterised in the present study has potential to be used in breeding programs aimed at improving wheat grain quality.